2018
DOI: 10.1007/s13205-018-1447-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of anthocyanin biosynthesis genes in Daucus carota callus culture in response to ammonium and potassium nitrate ratio in the culture medium

Abstract: Anthocyanins are major water-soluble and dynamic colouring plant pigment present in plant tissues with the high antioxidant properties. The role of ammonium and potassium nitrate in the culture medium on anthocyanin augmentation is probed thoroughly, but the mechanism of its biosynthesis continues to be unclear. Hence, the present study was undertaken to optimise nitrate ratio in the culture medium for anthocyanin augmentation and examination of its biosynthesis pathway in callus culture of Daucus carota. MS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Additionally, N starvation promoted anthocyanin accumulation in grape callus [ 42 ]. In contrary, other reports showed that the increase of total N content by doubling KNO 3 in the MS medium increased anthocyanin content by 135% [ 12 ], which was congruent with results showing the highest accumulation of anthocyanins using an elevated N amount (70 mM) in the medium [ 43 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Additionally, N starvation promoted anthocyanin accumulation in grape callus [ 42 ]. In contrary, other reports showed that the increase of total N content by doubling KNO 3 in the MS medium increased anthocyanin content by 135% [ 12 ], which was congruent with results showing the highest accumulation of anthocyanins using an elevated N amount (70 mM) in the medium [ 43 ].…”
Section: Discussionsupporting
confidence: 73%
“…Hairy roots of carrot, red beet, and madder in the presence of NH 4 + available in the amounts in the MS medium had a reduced growth [ 45 ]. A similar effect of restricted growth was observed for anthocyanin accumulating carrot callus cultured on MS [ 12 ]. No growth changes were reported only when carrot cell suspension was exposed to a doubled amount of ammonium N form than present in MS [ 46 ].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the present study, of grape berries, it is clear that the development of the anthocyanin contents is firmly associated with the biosynthetic genes expression pattern. There are two classes of enzymes elaborating the biosynthesis pathways-early genes that comprise of- phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumaroyl:CoA-ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavanone 3-hydroxylase (F3H), flavonoid 3′5′-hydroxylase (F3′H), and late genes-dihydroflavonol reductase (DFR), anthocyanidin synthase (ANS), also called leucoanthocyanidin dioxygenase (LDOX) and UDP glucose:flavonoid-3- O -glucosyltransferase (UFGT) [ 76 ]. A previous study has described the ammonium nitrate and potassium nitrate effects on pathway genes of anthocyanin [ 77 ].…”
Section: Discussionmentioning
confidence: 99%